2020
DOI: 10.3390/foods9121724
|View full text |Cite
|
Sign up to set email alerts
|

Are Dietary Lectins Relevant Allergens in Plant Food Allergy?

Abstract: Lectins or carbohydrate-binding proteins are widely distributed in seeds and vegetative parts of edible plant species. A few lectins from different fruits and vegetables have been identified as potential food allergens, including wheat agglutinin, hevein (Hev b 6.02) from the rubber tree and chitinases containing a hevein domain from different fruits and vegetables. However, other well-known lectins from legumes have been demonstrated to behave as potential food allergens taking into account their ability to s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(11 citation statements)
references
References 109 publications
0
11
0
Order By: Relevance
“…In addition, since a thorough risk assessment is still lacking, the presence of antivitamins in crops may suffer from a lack of public acceptability. The low success of lectin-expressing plants is likely because these proteins are potential food allergens (Barre et al 2020). Although they proved to be very effective against pests, especially when fused with proteins from insect specific and even insect pest-specific arthropod venoms, no impact on beneficial insects has been observed (Gatehouse et al 2011;Nakasu et al 2014).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, since a thorough risk assessment is still lacking, the presence of antivitamins in crops may suffer from a lack of public acceptability. The low success of lectin-expressing plants is likely because these proteins are potential food allergens (Barre et al 2020). Although they proved to be very effective against pests, especially when fused with proteins from insect specific and even insect pest-specific arthropod venoms, no impact on beneficial insects has been observed (Gatehouse et al 2011;Nakasu et al 2014).…”
Section: Discussionmentioning
confidence: 99%
“…Lectins or carbohydrate-binding proteins are widely distributed in seeds and vegetative parts of edible plant species. They are considered as potential food allergens, however, more investigations are needed to fully assess their allergenicity [ 40 ]. Soybean lectin is a species-specific single-copy gene, which is usually used as a target for the allergenic soybean detection [ 21 ].…”
Section: Discussionmentioning
confidence: 99%
“…It was shown that the expression of exogenous lectins in genetically engineered plants led to various detrimental effects in invading insects, ranging from a severe delay in development to high mortality rates. Moreover, the introduction of specific lectins to the insect diet negatively affects pest performance, as reviewed in [48]. The toxicity of lectins depends on the presence of specific carbohydrates in the insect body, which, in turn, is correlated with insects' developmental stage [49,50].…”
Section: Spectrum Of Latex Proteinsmentioning
confidence: 99%